The Seventh Nordic Workshop on Reindeer Research 1993 - Haugerud (ed.), Rolf Egil (Rangifer, 1995)
The meeting was arranged in Tromsø and it was hosted jointly by the Department of Arctic Biology, University of Tromsø and the Centre of Veterinary Medicine in Tromsø. The theme of the meeting was «Reindeer - Pastures and Environment in the Barents Euro Arctic Region (BEAR).»Approximately 70 persons attended.This NOR-meeting was held just after two big international conferences in Tromsø explaining the broad international participation.